2009
DOI: 10.1007/s00114-009-0575-0
|View full text |Cite
|
Sign up to set email alerts
|

Heat and carbon dioxide generated by honeybees jointly act to kill hornets

Abstract: We have found that giant hornets (Vespa mandarinia japonica) are killed in less than 10 min when they are trapped in a bee ball created by the Japanese honeybees Apis cerana japonica, but their death cannot be solely accounted for by the elevated temperature in the bee ball. In controlled experiments, hornets can survive for 10 min at the temperature up to 47 degrees C, whereas the temperature inside the bee balls does not rise higher than 45.9 degrees C. We have found here that the CO2 concentration inside th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 8 publications
1
46
0
Order By: Relevance
“…This finding suggested that Acks shares similar properties with the European honeybee neural IEG, kakusei . In addition, we also examined whether Acks upregulation after neural activation begins earlier under a higher temperature, because the temperature in the hot defensive bee ball rises to almost 47°C [6], [16]. In the bees awakened from anesthesia under the high temperature (46°C), Acks expression also peaked at 30 to 60 min (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggested that Acks shares similar properties with the European honeybee neural IEG, kakusei . In addition, we also examined whether Acks upregulation after neural activation begins earlier under a higher temperature, because the temperature in the hot defensive bee ball rises to almost 47°C [6], [16]. In the bees awakened from anesthesia under the high temperature (46°C), Acks expression also peaked at 30 to 60 min (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the formation of a hot defensive bee ball is a highly adaptive anti-predator behavior. Because there is only 3–5°C difference in the lethal temperature between the Japanese honeybee and the giant hornet [6], [16], accurate monitoring and precise control of heat generation during forming a hot defensive bee ball seem critical for the Japanese honeybees. In insect, the mechanism of temperature sensing has been studied mainly in Drosophila melanogaster and is known to depend on some transient receptor potential (TRP) channels [32][34].…”
Section: Discussionmentioning
confidence: 99%
“…In heat-balling the wasp succumbs to the heat inside the ball because hornets and wasps have a lower thermal tolerance than bees [30,31]. In asphyxia-balling , the heat inside the ball can be lethal to the predator but it dies due to the increased concentration of CO 2 in the hemolymph which causes asphyxiation [32,33]. …”
Section: Methodsmentioning
confidence: 99%
“…5), similar to previously reports. 15,21,22) On the basis of some reports, 15,23,24) we speculate that the optimal activity for rDPP-IV involves important physiologic mechanisms of V. basalis, such as defense or antagonist of the external stress.…”
Section: Discussionmentioning
confidence: 77%